De Daqui Prali para daquiprali: uma leitura corpomídia dos fluxos da comunicação corpo-cidade - Ferreira, Viviane Karine Gomes (2013)
The urban landscapes of cities do not appear at first glance. Much remains in its corners and its folds, especially when it comes to body communication with the city. This dissertation deals with a communication permeated with recesses, which is being investigated in the light of contributions indisciplinares and interdependent: Theory Corpomídia; (Katz & GREINER, 2001, 2005, 2010), which is positioned as the main theoretical basis of this work; Theories communication (SODRÉ, 2011; Martin-Barbero, 2004) and reading about the city (SANTOS, 2001; D' ALESSIO FERRARA (2007, 2008). With methodology theoreticalpractice, this study has been made of the fabric crisscrossed between the literature review and case study of intervention daquiprali dance, which was held in the center of the city of São Paulo, from august 2011 to april 2013. The objective of this research is to investigate, understand and test the possibilities of intervertebral city since the same shows as the media environment, bringing out traits and pathways acquired by polluting processes, promoted by exchanges with the environment, of which the body does not abstracts and whose cultural characteristics occupy a preponderant role. So that if is necessary to establish the geographical limits studied. Took the path between the Cathedral Square to the Largo de Santa Cecilia, as well as their surroundings. Conclude that the body acts as a bookie communication processes possible, transforming themselves and the environments in which it operates